Athanas philippei n. sp., a new alpheid shrimp associated with stomatopods in New Caledonia (Decapoda: Caridea) - Anker, Arthur; Ďuriš, Zdeněk (Zootaxa, 2022)
A new stomatopod-associated species of the alpheid shrimp genus Athanas Leach, 1814 is described based on several specimens collected in shallow waters of northern New Caledonia. Athanas philippei n. sp. differs from all of its congeners by a unique combination of morphological characteristics, as well as a diagnostic colour pattern. All specimens of A. philippei n. sp. were collected from burrows, including one with its host, a large tiger mantis shrimp, Lysiosquillina maculata (Fabricius, 1793) (Lysiosquillidae). Thus, the new species represents the fifth species of Athanas known or presumed to be associated with the spacious burrows of stomatopods.